Kierunki usprawnień gospodarki oraz organizacji w aspekcie zarządczym i prawnym - Redakcja (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2024)
Książka przeznaczona jest dla menadżerów, prawników ekonomistów oraz osób interesujących się trendami, a także koniecznymi do przeprowadzenia zmianami w obszarze zarówno regulacji prawnych, jak i praktyk organizacyjnych i zarządczych. Publikacja przedstawia wybrane zagadnienia z perspektywy ekonomicznej oraz prawnej, co powoduje swoistego rodzaju synergię płaszczyzn oceny. The publication is of special interest to managers, lawyers and people who are interested in contemporary trends and necessary changes in the area of both legal regulations and organisational and management practices. By presenting selected issues from both the economic and legal perspectives, it generates a kind of synergy of management and law science.
Directions of economic and organisational improvements in managerial and legal aspects
Keywords: organizacja; gospodarka; prawo; trendy; dostosowanie; organization; economy; law; trends; adjustment